Agreeing on the future: Long term transport planning in Copenhagen - Endres, Jean Paulo (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
To make long term forecasts include a considerable amount of uncertainty. In this paper, a short review of some of the methods used to forecast mobility demand and planning is made and their strengths and flaws are briefly discussed. For planning Copenhagen’s mobility for the years beyond 2050, the “Future Workshop” was chosen in order to organize a workshop among young mobility and city planning interested persons in Copenhagen. In the workshop three different future visions were elaborated and later analyzed under the Triple Access System theory prism. Among the three envisaged futures, two of them seem to imply and increase in physical mobility demand, while one expects a reduction in physical mobility demand, which will be substituted by increased spatial proximity and digital connectivity.